(untitled) (Zien Journal of Social Sciences and Humanities, 2022)
This article analyzes changes, which occur in Algerian political life, as well as threats of terrorists and interests of the outside forces toward Algeria. Religious extremists of the previous age led to Civil war in this region. However, successful operations of Algeria against terrorist lead to cooperation with neighboring countries and fight against terrorists.